Cognitive interference elicits developmental sex differences in inhibitory control - Jake J. Son; Abraham D. Killanin; Mikki Schantell; Yasra Arif; Thomas W. Ward; Maggie P. Rempe; Grace C. Ende; Hannah J. Okelberry; Danielle L. Rice; Anna T. Coutant; Julia M. Stephen; Yu-Ping Wang; et al. (Developmental Cognitive Neuroscience)
Inhibitory control is a key component of cognitive control that enables children and adolescents to develop increasingly complex skills throughout development. These processes are subject to insult via endogenous and environmental stressors (e.g., puberty, trauma) and alterations can lead to significant behavioral impairments that persist into adulthood. Despite this, the normative developmental course of neural oscillatory activity underlying interference control, a critical subcomponent of inhibitory control, and potential sex differences along this course, remain poorly understood. Herein, we utilized high-density magnetoencephalography (MEG) during the Eriksen flanker task to map the developmental sensitivity of neural processes supporting interference control in a large sample of children and adolescents (N = 121). MEG data were transformed into the time-frequency domain and significant oscillatory responses were imaged using a beamformer. Whole-brain analysis of flanker interference maps (i.e., incongruent - congruent trials) revealed age-related decreases in theta power in the supplementary motor area and cerebellum. Furthermore, regions known to be critical for supporting cognitive control, including the prefrontal and parietal cortices, exhibited age-by-sex interactive effects, suggesting modulation of interference control throughout development in a sex-dependent manner. Taken together, these data contribute to the characterization of the electrophysiological mechanisms supporting the development and refinement of interference control.